Mössbauer and XPS spectroscopies studies of SMSI effect on Fe/Nb2O5 catalysts for the Fischer-Tropsch synthesis - Cagnoli, Maria Virginia (2007)
In order to study if the SMSI effect produces benefitial results on the Fischer-Tropsch (FT) reaction using the Fe/Nb2O5 system we prepared two catalysts by reduction at two different temperatures. The solids were characterized by Mössbauer spectroscopy, XRD, XPS, N2 adsorption, atomic absorption, CO chemisorption and volumetric oxidation. It was demonstrated that the support is partially reduced leading to a covering of the Fe° crystals by NbOx species. At the higher reduction temperature studied (773 K) this effect produced a very important activity decrease, an increase in methane production and a shift of the product distribution towards to higher molecular weight hydrocarbons. © 2007 Elsevier B.V. All rights reserved.